2005
DOI: 10.1128/iai.73.3.1432-1440.2005
|View full text |Cite
|
Sign up to set email alerts
|

IpaD of Shigella flexneri Is Independently Required for Regulation of Ipa Protein Secretion and Efficient Insertion of IpaB and IpaC into Host Membranes

Abstract: Shigella flexneri causes human dysentery after invading the cells of the colonic epithelium. The best-studied effectors of Shigella entry into colonocytes are the invasion plasmid antigens IpaC and IpaB. These proteins are exported via a type III secretion system (TTSS) to form a pore in the host membrane that may allow the translocation of other effectors into the host cytoplasm. TTSS-mediated secretion of IpaD is also required for translocation pore formation, bacterial invasion, and virulence, but the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
202
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(211 citation statements)
references
References 42 publications
7
202
1
1
Order By: Relevance
“…The needle is ϳ50 nm in length, has an outer diameter of 7.0 nm, and possesses an inner channel that is ϳ2.0 -3.0 nm in diameter (10,11). We recently demonstrated that invasion plasmid antigen D (IpaD) localizes to the tip of the TTSA needle (12), where it controls secretion of the translocator proteins IpaB and IpaC and directs their insertion into host cell membranes (13). From its position at the TTSA needle tip, IpaD is responsible for recruiting and stably maintaining IpaB to this site in the presence of bile salts (14).…”
Section: From the Department Of Molecular Biosciences University Of mentioning
confidence: 99%
See 4 more Smart Citations
“…The needle is ϳ50 nm in length, has an outer diameter of 7.0 nm, and possesses an inner channel that is ϳ2.0 -3.0 nm in diameter (10,11). We recently demonstrated that invasion plasmid antigen D (IpaD) localizes to the tip of the TTSA needle (12), where it controls secretion of the translocator proteins IpaB and IpaC and directs their insertion into host cell membranes (13). From its position at the TTSA needle tip, IpaD is responsible for recruiting and stably maintaining IpaB to this site in the presence of bile salts (14).…”
Section: From the Department Of Molecular Biosciences University Of mentioning
confidence: 99%
“…This mutation also prevents polymerization of needles in vivo, resulting in secretion of MxiH C⌬5 monomers but a phenotype that is otherwise like a mxiH null mutant (19). To obtain uniformly 15 N, 13 Clabeled MxiH C⌬5 , mxiH⌬5/pET22b in E. coli Tuner(DE3) was grown in minimal medium supplemented with 15 N NH 4 Cl and 13 C-glucose as the sole nitrogen and carbon sources, respectively (21). After reaching mid log phase, bacteria were induced to produce protein with 1 mM isopropyl-1-thio-␤-D-galactopyranoside and grown at 15°C overnight.…”
Section: C⌬5mentioning
confidence: 99%
See 3 more Smart Citations